Enhancing soil quality and economic value in oil palm plantations: effects of livestock integration on earthworm abundance and ecosystem services - Al-Saedi, Thaer Kareem; Sayed, Khalid; Syakir, M.I.; Umar, Yarima; Azhar, Badrul; Tohiran, Kamil A.; Nobilly, Frisco; Rahmat, Siti Rahyla (Elsevier GmbH, 2025)
The adoption of livestock integration practices in sustainable Oil Palm Plantations (OPP) is essential for preserving soil quality and enhancing the Economic Value (EV) associated with earthworms, which play a vital role in soil Ecosystem Services (ES). Therefore, there is a necessity to study the presence and role of earthworms in response to different weed management practices in OPP. Using a hand sorting approach, this study explores the abundance and distribution of earthworms within Systematic Grazing Practices (SGP), Free-range Grazing Practices (FGP), and Herbicide Practices (HP). Additionally, the EV of earthworms was estimated using a market price strategy. A two-way Analysis of Variance (ANOVA) demonstrated a significant relationship (p < 0.0001) between management practices and earthworms’ abundance and activities in all plots. SGP showed a notable abundance of 79 ind./m2, with earthworm activity distributed across the soil layers. The earthworm activity in SGP demonstrates 25 ind./m2 adults and 54 ind./m2 juveniles with significant cast production of 580 casts/m2 and cast biomass 2950 g/m2. Regarding FGP, the earthworm community was found to be 40 ind./m2, with cast production at 205 casts/m2 and a biomass of 671 g/m2. In comparison, HP exhibited only 21 ind./m2. with cast production at 40 casts/m2 and a mere biomass of 102 g/m2. The estimated Present Value (PV) for SGP is $108,600 ha/y, and the future value (FV) will project at $168,500 ha/y-10. The results highlight the critical role of SGP in enhancing soil ecosystem services through earthworm activities in OPP. The study also successfully demonstrated that earthworms play a direct role in improving soil health over time. By employing appropriate models and conducting mesoscale studies. This could help shed some light on what was previously a “black box” in soil health rehabilitation.